A comparison between Emergency Calls over 4G and 5G Network Slicing - Damasceno, Maria G. Lima; Arnez, Jussif J. Abularach; Reis, Renata K. Gomes Dos; Souza, Caio B. Bezerra De; Gomes, Jéssica Da Silva; Gomes, Isaac A. Barros (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2024: Anais Estendidos do XLII Simpósio Brasileiro de Redes de Computadores e Sistemas DistribuídosDO - 10.5753/sbrc_estendido.2024.1704, 2024)
Emergency calls (eCall) via IP Multimedia Subsystem (IMS) were already used in Fourth Generation (4G) mobile networks so they were provided in high-definition (HD) voice calling. With the evolution to Fifth Generation (5G) networks, the concept of Network Slicing (NS) was introduced where the IMS network and its services are part of the Enhanced Mobile Broadband (eMBB) slice. This article seeks to compare the Quality of Service (QoS) of emergency calls over 4G and 5G by applying the eMBB slice. The results present the evaluation of QoS metrics i.e. packet loss, throughput and jitter for each eCall architecture, demonstrating the best performance of 5G in terms of QoS.